Potamonautes nheenae, a new species of freshwater crab from Gabon, Central Africa, with a description of the first known male of Erimetopus brazzae (A. Milne-Edwards, 1886) from the Democratic Republic of the Congo, Central Africa (Brachyura: Potamoidea: Potamonautidae) - Cumberlidge, Neil (Zootaxa, 2017)
A new species of the freshwater crab genus Potamonautes MacLeay, 1838, is described from Ivindo National Park in Sofala Province, Gabon, Central Africa. Potamonautes nheenae n. sp. is morphologically distinct from the other species of this genus found in Gabon and nearby countries in Central Africa, and is most closely related to P. paecilei (A. Milne-Edwards, 1886) from the Lower Congo River basin in the Democratic Republic of the Congo. The new species is recognised by a unique combination of morphological characters of the adult male first gonopod, anterior sternum, mouthparts, and major cheliped. Illustrations of P. nheenae n. sp. are provided and differences with congeners found in Central Africa are discussed. In addition, the male gonopods, pleon, and sternum of the unusual freshwater crab Erimetopus brazzae (A. Milne-Edwards, 1886), are illustrated for the first time since its description in 1886, following the discovery of the first known male specimen of this species in the collection of the Museum of Comparative Zoology at Harvard University.